鷹架具體程度對創意發想的影響 A Discussion on Scaffolding Theory and Online Game Design Task Creativity - 于文正 Wen-Cheng Yu (National Taiwan Normal University, 2014)
本研究採準實驗設計，研究教學鷹架對於學生創意作業的影響。參與研究的是119 位北部某技術學院選修「創造力與生活」課程的學生，學生依選課班級被隨機分派為實驗組與控制組。前測顯示兩班學生在對教師的教學反應、修課前的興趣與課程專注力上均無差異。實驗處置是創意作業指導上不同程度的具體性，實驗組須嚴格依照明確、具體的鷹架指導刺激創意發想，之後完成創意作業，控制組則採用鬆散的教學鷹架，擁有充分自由度去發揮。創意作業由3 位創造力教育專家針對「獨特性」、「豐富性」及設計概念的「整體性」三項指標評分，雖然t 檢定的結果顯示兩組並無差異，但若以各組創意作業得分等第的分布進行比較，則實驗組的創意作業在獨特性與豐富性上均比控制組好，控制組僅在創意作業的整體性上與實驗組表現接近。 In this study, a quasi-experimental design was applied to understand the influence of scaffolding instructions on student performance in executing a creative online gaming task. A total of 119 students enrolled in the "Creativity and Living" course at a technology college in Northern Taiwan participated in this study. The students were randomly divided into experimental and control groups based on their optional classes. An investigation conducted prior to the experiment indicated that the students in the two groups did not display differences in their reactions to teachers' instructions, their interest in the course before it commenced, or in their level of attention during the courses. The experimental intervention involved following various instructions for performing a creativity task titled "Online Gaming Concept Design." Because the scaffolding instructions for the control group were more lenient than those for the experimental group were, the students in the control group had a comparatively higher degree of freedom when working on the creative task. Conversely, the experimental group strictly adopted specific and detailed scaffolding rules to achieve their goal. Their creativity operation performance was evaluated using three creativity education specialists on the basis of three indices: uniqueness, diversity, and the integrity of the design concept. The results of the t test indicated no difference in the two groups, but the distribution of their scores was compared. Ranking the creative tasks revealed that the performance of students in the control group was limited by their capacity for imagination, and the diversity and details were lacking, but the experimental group demonstrated excellent innovation, high diversity, and presented a degree of integrity.